Retorika Perlawanan dalam “Shout wa Suut”: Analisis Stilistika Puisi Mahmoud Darwish - Adnan, Nab’han Hadyan; Ardhillah, Isma Annisa Nur; Maulana, Kukuh Favian; Sudarmawan, Habib Muharrom (Prosiding Konferensi Nasional Bahasa Arab, 2024)
Mahmud Darwish's poetry often talks about resistance in a subtle way, but this poem titled “صوت وسوط” embodies an assertive type of resistance. Therefore, the purpose of this research is to comprehend how personification, synecdoche, metaphor, and other figures of speech are used to accentuate the topic of resistance. It was discovered through stylistic study that diction, imagery, and rhyme all contribute significantly to the development of deep meanings related to Palestinian identity and struggle. The poem contains an assertive resistance language style that is seen through figurative language consisting of metaphor, hyperbole, personification, repetition, paradox, irony, euphemism, antithesis, parallelism, sarcasm and rhetoric. Then various imagery which includes visual, auditive, tactile, kinesthetic and olfactory imagery. There are also concrete words such as lightning and clouds, waves and storms, sun, horses, fields and plows, flags, earth, blood, hills, spears, vineyards, ladders, crosses, and whips.غالبًا ما يتحدث شعر محمود درويش عن المقاومة بطريقة خفية، لكن هذه القصيدة التي تحمل عنوان ”صوت وسوط“ تجسد نوعًا من المقاومة المؤكدة. ولذلك، فإن الغرض من هذا البحث هو فهم كيفية استخدام التجسيد والتشبيه والاستعارة وغيرها من أشكال الكلام لإبراز موضوع المقاومة. وقد تبيّن من خلال الدراسة الأسلوبية أن الإلقاء والصور والقافية تسهم جميعها بشكل كبير في تطوير المعاني العميقة المتعلقة بالهوية الفلسطينية والنضال الفلسطيني. وتتضمن القصيدة أسلوباً لغوياً مقاوماً حازماً يتجلى من خلال اللغة التصويرية التي تتألف من الاستعارة، والمبالغة، والتجسيد، والتكرار، والمفارقة، والمفارقة، والسخرية، والتلطف، والتضاد، والتوازي، والسخرية، والبلاغة. ثم الصور المتنوعة التي تشمل الصور البصرية والسمعية واللمسية والحركية والشمية. وهناك أيضاً الكلمات الملموسة مثل البرق والغيوم، والأمواج والعواصف، والشمس، والخيل، والحقول والمحاريث، والأعلام، والأرض، والدم، والتلال، والرماح، والكروم، والسلالم، والصلبان، والسياط.